Evaluation of biomaterials with and without platelet-rich plasma: a histometric study using beagle dogs - Oliveira, Brunamelia De; Assunção, Wirley Gonçalves; Zanoni, Jacqueline Nelisis; Camarini, Edevaldo Tadeu; Okamoto, Roberta (Faculdade de Odontologia de Piracicaba - UNICAMP, 2015)
AbstractAim:To compare the alveolar bone repair process using biomaterial in dogs with and without the incorporation of platelet-rich plasma.Methods:Six beagles were used. Bilateral extractions of the three mandibular premolars were performed. Bio-Gen(r) was applied in the first alveolus, the clot was maintained in the second alveolus and Genox(r) was applied to the third alveolus. PRP was added to all alveoli on the left side only. The dogs were submitted to euthanasia after 30, 60 and 90 days and submitted to histological analysis for the determination of mean area of new bone formation. Tukey's post test was used in the statistical analysis.Results:Significant increase in bone formation occurred in Bio-Gen(r) + PRP when compared with the other groups at 30 and 90 days. In the evaluation at 60 days, no statistically significant differences among the groups were found.Conclusions:The Bio-Gen(r) biomaterial led to the best bone repair and the combination of platelet-rich plasma accelerated the repair process.
Keywords: biocompatible materials; platelet-rich plasma; bone regeneration